What is an author like Borges? Relation between "The Library of Babel" and the theory of Michel Foucault. - Cavallin, Claudia V (Journal of English Language and Literature (ISSN: 2368-2132), 2018)
Foucault talks about the relation of attribution, where Borges can be attributed everything related with things that he said or written. In this essay I define the actions in the name of an author like Borges, related to the category of the proper name. His name is more than a gesture, is part of his connexion between words and things. As Foucault says, Borges is the author of a novel and he is responsible for more than his own text. Borges use connections, different types of discourse and the author's position in a discursive field. The author's name may be relevant in certain circumstances and I would like to define that kind of circumstances in Borges.